Characterization of Microbial Communities in Pilot-Scale Constructed Wetlands with Salicornia for Treatment of Marine Aquaculture Effluents. (29th April 2018) - Ma, Xiaona; Song, Xingqiang; Li, Xian; Fu, Songzhe; Li, Meng; Liu, Ying
Abstract : Microorganisms play an essential role in the performance of constructed wetlands (CWs) for wastewater treatment. However, there has been limited discussion on the characteristics of microbial communities in CWs for treatment of effluents from marine recirculating aquaculture systems (RAS). This study is aimed at characterizing the microbial communities of pilot-scale CWs with Salicornia bigelovii for treatment of saline wastewater from a land-based Atlantic salmon RAS plant located in Northern China. Illumina high-throughput sequencing was employed to identify the profile of microbial communities of three CWs receiving wastewater under different total ammonia nitrogen (TAN) concentrations. Results of this study showed remarkable spatial variations in diversity and composition of microbial communities between roots and substrates in three CWs, with distinct response to different TAN concentrations. In particular, Proteobacteria, Firmicutes, Cyanobacteria, and Bacteroidetes were predominant in roots, while Cyanobacteria, Proteobacteria, Firmicutes, Verrucomicrobia, and Bacteroidetes were prevalent in substrates. Moreover, redundancy analysis indicated that specific functional genera, such as Nitrosopumilus, Vibrio, Pseudoalteromonas, Nitrospina, and Planctomyces, played key roles in the removal of nitrogen/phosphorus pollutants and growth of wetland plants. From a microorganism perspective, the findings of this study could contribute to better understanding of contaminants' removal mechanism and improved management of CWs for treatment of effluents from land-based marine aquaculture.